Quality indicators in requirements elicitation - Krishna, Aneesh; Gregoriades, Andreas; Sombattheera, Chattrakul (My University, 2010)
Domain knowledge is found to be a crucial factor in attaining quality of requirements. System analysts, who have adequate knowledge of software often don't usually understand the organizational context well. This paper, presents a novel approach that utilizes the Tropos, Software System-Business Model (SS-BM) to requirements list elicitation. In the proposed method, requirements items are mapped to SS-BM elements based on their semantic meanings. The mapped requirements list and SS-BM are analyzed in specific sequence according to multiple checking points. Problems with the requirements list are identified in the analysis process and possible improvements are proposed. Quality indicators are used to summarize the quality of requirements at the end of the elicitation process.
Keywords: Analysis process; Business models; Checking point; Domain knowledge; Organizational context; Specific sequences